Changes in staff confidence and attributions for challenging behaviour after training in positive behavioural support, within a forensic mental health setting: a replication study with follow-up. Issue 6 (1st November 2016) - Davies, Bronwen; Griffiths, John; John-Evans, Hannah; Lowe, Kathy; Howey, Sarah; Artt, Alexandra
Abstract: Positive behavioural support (PBS) is a proactive approach to managing challenging behaviour. Staff in a forensic mental health service were provided training in PBS. The study aimed to assess the effectiveness of training by measuring changes to staff confidence and attributions for challenging behaviour before training, post training and at six-month follow-up. Qualified and unqualified staff were compared, as were male and female staff. Confidence was measured using an adapted version of the Confidence in Coping with Patient Aggression Instrument. The Challenging Behaviour Attributions Scale and the Causal Dimension Scale II assessed staff attributions. Staff confidence levels in working with challenging behaviour increased following PBS training, and this increase was maintained at six-month follow-up, for unqualified, qualified, male and female staff. Changes in attributions for challenging behaviour were observed post training; however changes were not maintained at follow-up. Limitations and clinical implications were outlined.